Understanding consumer purchase intention for halal street food in South Korea: a case study of Malaysian Muslim travellers - Abu Bakar, Ahmad Redhuan; Hamzah, Halipah; Azman, Aida Syazwina; Mohd Sufian, Nurul Atikah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
The recent global increase in the Muslim population, coupled with a rising demand for halal food products, has contributed to the significant expansion of the global halal food market. This trend reflects a growing consumer interest in halal -certified products. South Korea has emerged as a popular travel destination among Muslim tourists, particularly those from Malaysia. However, challenges have surfaced concerning the misuse of halal signage by street food vendors who, in some instances, offer non-Halal items. This situation has raised concerns among Malaysian Muslim travelers regarding the authenticity and reliability of halal street food in the country. This study aims to investigate the purchase intentions of Malaysian Muslim travelers toward halal street food in South Korea by employing the Theory of Planned Behavior (TPB) as the guiding theoretical framework. The variables assessed in the study include attitude, subjective norms, perceived behavioral control, and consumer awareness. A total of 142 valid survey responses were collected and quantitatively analysed. The overall reliability and validity test of Cronbach’s Alpha score is 0.911, indicating excellent internal consistency. Spearman correlation analysis revealed weak yet positive correlations between the independent variables and purchase intention: attitude (0.142), subjective norms (0.137), perceived behavioral control (0.029), and consumer awareness (0.179). These findings suggest that although the correlations are modest, there is a meaningful association between the examined variables and the purchase intentions of Malaysian Muslim travelers with regard to halal street food in South Korea. The results underscore the need for a structured and reliable halal support system in South Korea. Enhancing the halal food ecosystem would assist regulatory authorities and tourism agencies in implementing effective strategies to address these concerns. Such measures would not only improve the availability and authenticity of halal street food but also foster greater confidence among Muslim travelers when making food-related decisions.